Oxytocinergic Cells of the Hypothalamic Paraventricular Nucleus Are Involved in Food Entrainment - Caba, Mario; Huerta, César; Meza, Enrique; Hernández, Manuel; Rovirosa-Hernández, María J. (Frontiers in Neuroscience, 2020)
When food is presented at a specific time of day subjects develop intense locomotor behavior before food presentation, termed food anticipatory activity (FAA). Metabolic and hormonal parameters, as well as neural structures also shift their rhythm according to mealtime. Food-entrained activity rhythms are thought to be driven by a distributed system of central and peripheral oscillators sensitive to food cues, but it is not well understood how they are organized for the expression of FAA. The hormone Oxytocin plays an important role in food intake, satiety and homeostatic glucose metabolism and although it is recognized that food is the main cue for food entrainment this hormone has not been implicated in FAA. Here we investigated the activity of oxytocinergic (OTergic) cells of the hypothalamus in relation to the timing of feeding in rabbit pups, a natural model of food entrainment. We found that OTergic cells of the supraoptic nucleus and the main body of the paraventricular nucleus (PVN) are activated after feeding which suggests that OT may be an entraining signal for food synchronization. Moreover, a detailed analysis of the PVN revealed that OTergic cells of the caudal PVN and a subpopulation in the dorsal part of the main body of this nucleus shows activation before the time of food but not 12 hours later. Moreover this pattern persists in fasted subjects at the time of the previous scheduled time of nursing. The fact that those OTergic cells of the dorsal and caudal part of the PVN contain preautonomic cells that project to the adrenal, pancreas and liver perhaps may be related to the physiological changes in preparation for food ingestion, and synchronization of peripheral oscillators, which remains to be determined; perhaps they play a main role in the central oscillatory mechanism of FAA as their activity persists in fasted subjects at the time of the next feeding time.